SISTEM PAKAR DIAGNOSA PENYAKIT MALARIA PADA RSUD TANI DAN NELAYAN KABUPATEN BOALEMO - Irvan Muzakkir (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2016)
Malaria is an infectious disease caused by parasites of the genusPlasmodium, which is transmitted through the bite of Anopheles mosquitowith an overview of the disease include fever are often periodic, anemia,enlargement of the spleen and various collection of symptoms due to effectson several organs such as brain, liver and kidneys. Because malaria is verydangerous, the authors designed a malaria disease diagnosis expert systemthat allows users to diagnose the onset of her illness. Expert systems arecomputer programs that mimic an expert reasoning with expertise in aparticular knowledge area. Expert system trying to find a solution, giveadvice or conclusion that is consistent with thethe problems it finds. Theauthor managed to implement a web-based expert system uses backwardchaining method that can overcome these problems in consultation with thepatient. Programming languages used in this system is the PHPprogramming language and for database creation using mysq. Hope theauthor, this system can help physicians or even ordinary people in makingdecisions when diagnosing malaria. Based on the results of white box testingconcluded that this expert system error-free program for a total ofCyclomatic Complexity = 4, Region = 4, and Independent Path = 4.